2015
DOI: 10.1016/j.celrep.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Reconstruction of the Viral Evolutionary Lineage Yields a Potent Gene Therapy Vector

Abstract: SUMMARY Adeno-associated viral vectors (AAV) have emerged as a gene delivery platform with demonstrated safety and efficacy in a handful of clinical trials for monogenic disorders. However, limitations of the current generation vectors often prevent broader application of AAV gene therapy. Efforts to engineer AAV have been hampered by a limited understanding of the structure-function relationship of the complex multimeric icosahedral architecture of the particle. To develop additional reagents pertinent to fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
300
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(308 citation statements)
references
References 55 publications
5
300
1
2
Order By: Relevance
“…In line with previous findings, 18,19,21 DSF experiments showed that AAV5 was stable up to temperatures approaching 90 C (Tm = 87.4 C) and AAV9 denatured at 76.2 C. AAVrh32.33, a serotype that has not been previously studied, denatured at 64.6 C ( Figure 1B). These measurements were validated by IFS ( Figure 1C) and SDS-PAGE ( Figure 1D) experiments.…”
Section: Comparative Analysis Of Aav Capsid Thermostability Assayssupporting
confidence: 89%
See 1 more Smart Citation
“…In line with previous findings, 18,19,21 DSF experiments showed that AAV5 was stable up to temperatures approaching 90 C (Tm = 87.4 C) and AAV9 denatured at 76.2 C. AAVrh32.33, a serotype that has not been previously studied, denatured at 64.6 C ( Figure 1B). These measurements were validated by IFS ( Figure 1C) and SDS-PAGE ( Figure 1D) experiments.…”
Section: Comparative Analysis Of Aav Capsid Thermostability Assayssupporting
confidence: 89%
“…18 Major differences between the melting temperatures of naturally occurring AAV serotypes were observed (AAV2: melting temperature [Tm] = 69.6 C ± 0.5 C; AAV5: Tm = 89.7 C ± 0.7 C), 18 whereas reconstructed ancestral AAV particles exhibited enhanced thermostability in comparison to most of their contemporary, naturally occurring homologs. 19 In this study, we explore the possibility of using the biophysical measure of thermostability for AAV serotype identification at the protein level. We show, through the analysis of 67 AAV samples by DSF, that capsid thermostability can be used to discriminate AAV1, AAV2, AAV5, AAV6.2, AAV8, and AAV9 preparations, regardless of the packaged transgene and vector concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Given the spectrum of AAP phenotypes observed across the major clades, we similarly tested 9 putative evolutionary intermediates (AncAAVs) to the major AAV serotypes to gain insight into which elements of VP structure either impose the observed requirement for AAP or impart an ability for some VPs to perform these functions independently (Zinn et al, 2015). As with the nat ural serotypes, a broad range of requirements for AAP was observed for the AAPstop60 AncAAVs (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…This work was built on the assumption that ancestral AAVs were assembly-competent and that our computational and statistical modeling effort was able to approximate the molecular state of these putative evolutionary intermediates. Indeed, we predicted the primary structure of 9 putative bifurcation points within the lineages of AAV serotypes 1–3 and 6–9, each of which, to varying degrees, demonstrated assembly, viral genome packaging, and in vitro infectivity (Zinn et al, 2015). These reagents now provide us with a toolset to interrogate viral and vector phenotypes across much shorter genetic distances than previously possible.…”
Section: Introductionmentioning
confidence: 99%
“…At present, no experimental or computational approaches are available for engineering future antigenic variants of AAV before they emerge in nature. Earlier engineering strategies to address the problem of NAbs relied on the limited antigenic variability among different natural AAV isolates and yielded chimeric or ancestral AAV capsids (20)(21)(22). Complementarily, our approach explores the entire sequence space for each amino acid residue within antigenic footprints located on any AAV capsid surface.…”
Section: Discussionmentioning
confidence: 99%